Pengetahuan Dan Partisipasi Masyarakat Tentang Posyandu Ilp Melalui Edukasi Kesehatan Di Rt 07 Kelurahan Jalan Gedang Kota Bengkulu - Fatimah, Siti; RD, Anggun Torischa; Delitasari, Chosy; Putriana, Okta; Trisiska, Afleoni; Putri, Agitta Dwi; Wulandari, Wulandari (LPPM Universitas Dehasen Bengkulu, 2026)
The Integrated Health Post (Posyandu), categorized as a Primary Service Indicator (ILP), is a community-based health service that plays a crucial role in monitoring child growth and development, immunization, as well as maternal and child health prevention efforts (Ministry of Health RI, 2023). In the working area of Jalan Gedang Health Center, only 5 out of 71 households (223 residents) regularly attend Posyandu services, indicating a very low participation rate. This community engagement study aims to identify the contributing factors to low participation, analyze barriers—including knowledge, attitudes, access, and cadre support—and design promotive and preventive educational interventions to improve participation. The research used a pre-test and post-test design without a control group and involved 30 respondents. The results revealed a significant increase in knowledge scores, from an average of 50% (poor category) to 70% (good category) after the educational intervention. These findings demonstrate that education is effective in improving community understanding of the functions, benefits, and service types offered by Posyandu ILP. Furthermore, low participation is also influenced by limited community knowledge regarding Posyandu functions, consistent with the findings of Amanah (2021). It is concluded that educational interventions play an essential role in improving knowledge and enhancing community participation in utilizing Posyandu ILP services.